(untitled) (Revista Sistemas de Producción Agroecológicos, 2020)
In this work a thorough exploration is made to show the sheep production system as a productive and promising alternative for the near future of the of the Colombian tropical regions, correlated with the relevance presented at the national level in recent times and a viable socio-economic option for small children. producers of the population centers affected by the post-conflict; highlighting the lack of technology for this livestock link due to low productivity due to food management, ignorance of the species and the traditional bovine culture. With the revision of the bibliographic material and the contextualization of the intertropical region, the needs to emphasize, in order of importance, the efficient production of forages of high nutritional and biological value, a detailed genetic selection scheme analyzing the breed and its benefits are determined, and the competitive business vision for meat production. In addition to the most relevant factors to evaluate the efficiency of the diet, by means of the corporal condition and the sanitary status of the individuals. The foregoing favored, to conclude, the need to establish an integral technological package in the area, serving as a basis for the organization of current productions and the proper establishment of future sheep farms, from the nutritional aspect to the commercial factor.